Reliable placement of beetle fossils via phylogenetic analyses – Triassic Leehermania as a case study (Staphylinidae or Myxophaga?). (9th September 2019) - Fikáček, Martin; Beutel, Rolf G.; Cai, Chenyang; Lawrence, John F.; Newton, Alfred F.; Solodovnikov, Alexey; Ślipiński, Adam; Thayer, Margaret K.; Yamamoto, Shûhei
Abstract: Triassic fossils are rare but crucial for understanding the early evolution of large insect clades including beetles (Coleoptera). Their phylogenetic assignment is problematic because of fragmentary preservation, yet crucial for the correct use of the information they provide. Here an analysis is presented of the phylogenetic position of Leehermania prorova, the Late Triassic compressed fossil which was described and hitherto widely used as the oldest representative of Staphylinidae (rove beetles) in the suborder Polyphaga. By contrast with the intuitive character assessment made in the original description, a phylogenetic analysis of Leehermania is performed using an extensive morphological matrix of extant Coleoptera provided by the Beetle Tree of Life project, constrained in view of the latest relevant molecular phylogenies. As a result, Leehermania is identified as an extinct lineage within the beetle suborder Myxophaga, closest to the modern family Hydroscaphidae. Excluding Leehermania from Staphylinidae and placing it in Myxophaga amends erroneous assumptions about early diversification of rove beetles and enhances our views of the evolutionary history of Coleoptera. Abstract : Phylogenetic analysis based on morphological data and fixed tree topology of modern taxa according to molecular studies is introduced as a method suitable to test the phylogenetic position of fossils. Using this approach, the Late Triassic Leehermania is identified as an extinct lineage within the beetle suborder Myxophaga, closest to the modern family Hydroscaphidae, rather than in Polyphaga: Staphylinidae. Leehermania moves the minimum age of the Myxophaga documented by the fossil record back by 100 Ma.